Voluntary Intravenous Self‐Administration of Alcohol Detects an Interaction Between GABAergic Manipulation and GABRG1 Polymorphism Genotype: A Pilot Study. (20th July 2012) - Plawecki, Martin H.; Wetherill, Leah; Vitvitskiy, Victor; Kosobud, Ann; Zimmermann, Ulrich S.; Edenberg, Howard J.; O'Connor, Sean
Abstract : Background: Operant responding paradigms quantify a subject's motivation for reward, but such studies employing ingested alcohol cannot assure the same incremental increase in brain exposure to alcohol across subjects because of substantial variability in absorption kinetics. We developed a human progressive ratio (PR) paradigm using the computer‐assisted self‐infusion of ethanol (CASE) system that overcomes such variability and conducted a pilot study to assess its utility for detecting an interaction of subjects' GABRA2 or GABRG1 genotype and pretreatment with 1 mg of lorazepam (LZ) vs. placebo on their willingness to work for alcohol rewards. Methods: Twenty healthy, nondependent drinkers, aged 21 to 27, were balanced on rs279871 and rs2350439 single nucleotide polymorphisms in the GABRA2 and GABRG1 genes, respectively. Subjects worked for alcohol, with water as an alternative reinforcer (AR), using a progressive schedule of a task that required constant attention and adapted to both fatigue and drug effects. Testing began 1 hour after pretreatment with 1 mg LZ or placebo in a crossover design. Results: The CASE system performed well, and the constant attention task was perceived as work by all subjects. GABRA2 homozygosity did not significantly predict either breakpoint or cumulative work, whereas a significant GABRG1 genotype by LZ pretreatment interaction for cumulative work was detected ( p  =   0.04). Breakpoint revealed a weak trend toward pretreatment drug effects ( p  =   0.11), and a somewhat stronger interaction of LZ pretreatment with GABRG1 genotype ( p  =   0.06). GABRG1 status revealed a more complex relationship with respect to motivation for alcohol with and without LZ pretreatment; AG and GG individuals worked more for alcohol under both pretreatment conditions, while AA individuals worked more for the AR. Conclusions: The CASE PR paradigm shows promise as a laboratory method for use in drug development and phenotyping studies.